Pediatric cardiac services in Sudan: Achievements, challenges, and future perspectives (2004–2021) - Ali, Sulafa; Medani, Mohamed Eamin A.M.E. (Frontiers in Pediatrics, 2022)
Pediatric cardiology (PC) is a rapidly advancing specialty addressing a large population of children as well as adults with congenital heart disease. It requires huge technical and financial resources; therefore, establishing, maintaining, and developing such services in limited resource settings are challenging. A PC program that includes clinical aspects, echocardiography, diagnostic and interventional cardiac catheterization and cardiac surgery, and rheumatic heart disease control was established in Sudan in 2004. There are currently three public centers with facilities to evaluate and treat children with heart disease: two in Khartoum and one in Wad Medani. Major obstacles include the shortage of trained personnel and operation rooms, the deficiency of intensive care facilities, and the financial burden of interventional procedures. This paper details the establishment and progress of the program, its challenges, potential solutions, and future perspectives for PC programs in Sudan and African countries.